Public enemies: the host of America's most wanted targets - the nation's most notorious criminals - Walsh, John (Hall, 2001)
The host of America's Most Wanted, John Walsh has formed a vital partnership with the public, the media, and law enforcement that has led to the capture of hundreds of the worst serial killers, kidnappers, pedophiles, and rapists of our time. In Public Enemies he reveals the cost -- the blood, sweat, and tears -- behind the relentless pursuit of hard justice. In those and other gripping true-crime profiles, John Walsh exposes the behind-the-scenes drama of the groundbreaking show, and what actually unfolds between the crimes and the captures -- the vital leads from strangers, the dangerous manhunts, the developments cut from the AMW broadcasts, and the dogged investigations by authorities. He divulges stunning lapses in the judicial process that release monsters to the streets time and again. He takes readers inside the hearts and souls of the grieving families, and gives eyewitness accounts of the dramatic final moments when fugitives are finally taken down.